2021
DOI: 10.1139/cjce-2019-0471
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of design changes impact in healthcare construction projects using system dynamics

Abstract: Design changes (DC) contribute significantly to construction projects’ delays and cost overruns. Many research efforts tackled DCs management, yet with less efforts in healthcare construction (HC) projects which involve multiple stakeholders including medical users and require meeting engineering and medical specifications. Therefore, a new system dynamics model that simulates HC environment, considering engineering and medical factors that can potentially trigger DCs, was developed. It simulates, as well, DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Ansari [75] used SD to improve project planning by simulating change management policies for an Iranian construction project. Saad et al [76] used SD to simulate the ripple impact of design changes in healthcare construction projects, which can be used to allow proactive decision making for better design change management. Porwal et al [77] used SD to analyse the dynamic behaviour of system variables due to changes in the scope of works in order to minimize construction waste generation.…”
Section: Rework and Changementioning
confidence: 99%
“…Ansari [75] used SD to improve project planning by simulating change management policies for an Iranian construction project. Saad et al [76] used SD to simulate the ripple impact of design changes in healthcare construction projects, which can be used to allow proactive decision making for better design change management. Porwal et al [77] used SD to analyse the dynamic behaviour of system variables due to changes in the scope of works in order to minimize construction waste generation.…”
Section: Rework and Changementioning
confidence: 99%
“…Causes of design changes [20][21][22] Impact of design changes [23][24][25] In terms of research methods [26][27][28] The application of evolutionary game in green buildings…”
Section: Research Topics Dimensions Source Papersmentioning
confidence: 99%
“…Rahman [25] also confirmed that design changes in Malaysia are the main reason for project schedule and cost overruns. Saad et al [27] put forward a system dynamics model to capture the factors that may lead to engineering and medical-related design changes in healthcare projects and investigated the impact of these design changes on project performance. Afsharghotli and Yitmen [28] used the artificial neural network (ANN) model to evaluate the quantitative measurement of the time and cost performance of petrochemical projects caused by the interactive design change.…”
Section: Design Changes In Construction Projectsmentioning
confidence: 99%